Design and manufacture of insulation panels based on recycled lignocellulosic waste - Jensen, María Sol (2021)
This paper has been focused on the properties of construction material based on cellulose. More specifically, their use as non-bearing walls, coating-panels and/or anti-humidity panels. It has been obtained from the recycling of urban waste, such as paper and paperboard. The performance of this material has been evaluated in relation to five parameters: dimensional stability against humidity, fire action, decay resistance front fungal degradation, and, their behavior as temperature and acoustics isolation. The performance of manufactured materials has been verified considering environmental factors, and simulating the condition of the material in service. This yielded satisfactory results in relation to all the agents mentioned, which allows concluding that the material fulfills the desired function. It has been concluded that the designed and manufactured panels have the necessary characteristics to replace insulating materials or Gypsum plasterboard type enclosure, extending the range of materials for this function, through the incorporation of a new option based on recycled raw material, low-cost manufacture and minimal energy resources used.